Underwater photography - Friedrich, Tobias (Rocky Nook Inc., 2014)
Underwater photography is a fascinating pursuit for those who aspire to capture the magical world found within our oceans and bring it to the surface. In this book, award-winning photographer Tobias Friedrich teaches us how to create stunning underwater images, covering everything from the equipment needed, to creating powerful compositions, to processing the final image. He uses case studies to show how his own images were created, and provides detailed explanations for specific techniques that can be applied to your very next dive. The text is supported by images from some of the most beau.